Genetic Population of Hypothenemus hampei Ferarri (Coleoptera: Scolytinae) from Coffee (Coffea spp.) in Sumatra, Indonesia Using The Cytochrome Oxidase Subunit I Gene - Sitompul, Aida Fitriani; Dahelmi, Dahelmi; Roesma, Dewi Imelda (Bogor Agricultural University, Indonesia, 2025)
Hypothenemus hampei Ferrari, 1867, is a globally significant pest of coffee (Coffea spp.). Genetic information about H. hampei from various locations, including countries in America, Africa, and Asia (Java, Indonesia), is available. However, the data has yet to be available for Sumatra. This research aims to study the genetic population of H. hampei in coffee plants in Sumatra. In this study, a total of 27 mitochondrial cytochrome oxidase subunit 1 (COI) gene sequences were used to estimate the population genetics of H. hampei in Sumatra, collected from C. arabica, C. canephora, and C. liberica at nine locations. The analysis of the COI gene sequences revealed that they contained 236 base pairs (53.76%) of conserved sites, 203 base pairs (46.24%) of variable sites, 153 base pairs (34.85%) of parsimony sites, and 50 base pairs (11.38%) of informative single sites out of a total of 439 base pairs. Haplotype analysis of the COI gene in H. hampei from Sumatra revealed 10 haplotypes, with a haplotype diversity (h) of 0.649 and nucleotide diversity (π) of 0.004. Genetic differentiation (Fst) of H. hampei is low among populations in Sumatra. Genetic variation within populations is higher, and between populations is low. The genetic distance of 0-0.28%, 27 H. hampei sequences from Sumatra are in the same branch, indicating low genetic variation. This information holds great potential for designing sustainable control strategies to manage this pest species in coffee plants, particularly in the Sumatra region.